Trends in oncology marketing applications in the European Union: a five‐year systematic review - Basto, Ricardo; Karaya, Siddartha; Zwiers, Alex (Frontiers in Pharmacology, 2026)
In the European Union, before cancer medicines containing a new active substance become available to patients, they must undergo a rigorous authorization process through the Centralized Procedure. This study examines trends in oncology Marketing Authorization Applications (MAAs) over the past 5 years. Oncology MAAs from January 2020 to January 2025 were used to collect and analyze publicly available data. The number of MAAs, therapeutic indications, company and product characteristics, scientific advice (SA), orphan designation (OD)/expedited programs, and overall procedural time were analyzed. A total of 60 MAAs were identified. During the reporting period, only three MAAs received negative opinions; however, two were reverted to positive after re-examination. Blood cancers were the main therapeutic indication. The typical profile of a MAA was as follows: a large-sized company holder (72%); monoclonal antibody (mAb) (31%); SA requested (92%); under OD at both time points: at the moment of application (60%) and at the moment of receiving the opinion by the Committee for Medicinal Products for Human Use (67% of the initial number of MAAs under OD); not granted any expedited program (57%); and with an average total procedure time of about 348 days. Additionally, procedural time analysis revealed shorter timelines for MAAs under the accelerated assessment (AA) program and those that obtained SA. Oncology MAAs have increased over the years, particularly for mAbs and blood cancer indications. Large-sized companies were the main MAA holders. Additionally, the SA and AA program might have demonstrated a positive impact in reducing procedural time.